The Electoral Consequences of Corruption - de Vries, Catherine; Solaz, Hector (Annual Reviews, 2017)
Democratic elections have been assumed to play a crucial role in curbing corruption among public officials. Voters, due to their general distaste for corruption, are expected to sanction politicians who misuse public office for private gains. Yet, empirical evidence to date is mixed, and it often suggests that the electoral punishment of corruption is rather mild. Recently, political scientists have made great strides in understanding why corruption might be tolerated by voters. In this review, we identify three key stages—information acquisition, blame attribution, and behavioral response—that underlie a retrospective vote based on corruption. A breakdown of one or more of these stages may lead to a lack of electoral punishment of corruption. We also outline some areas for future progress, particularly highlighting the importance of voter coordination for understanding the extent to which corruption is punished at the ballot box.
Keywords: blame attribution; corruption; elections; political information; voting behavior; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades